Model Logit (Logistic Regression) Sebagai Model Probabilitas Linier Alternatif, Dalam Contoh Aplikasi Teknik Industri - Sugeng Santoso (Jurnal Teknik Industri, 2001)
Regression model in which the regressand evokes a yes or no or present or absent response are known as dichotomous, or dummy, dependent variable regression models. They are applicable in a wide variety of fields and are used extensively in survey or census-type data. Among the methods that are used to estimated such models, this paper considered three-LPM, logit and probit.